2018
DOI: 10.3906/vet-1707-80
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of biochemical parameters and oxidative stress in sheep naturally infected with Dicrocoelium dendriticum and hydatid cysts

Abstract: Introduction Parasitic diseases caused by liver trematodes have an important place among many parasitic infections causing reduced productivity in animals. Liver trematodes constitute an important parasitic group affecting domestic ruminants around the world and in Turkey. Animals infected by this parasite manifest symptoms such as deterioration of overall status, edema, anemia, and weakness. It has been reported that in infected animals the bile ducts are dilated, the gall bladder is filled with bile, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
4
6
0
Order By: Relevance
“…Thus, the graduated reduction in ALB and TP levels that are indicated in the current study seems to be associated with an increase in liver's hydatid cyst infection ratio, which may be caused by expand growing of hydatid cysts in the liver. In agreement with the current data, during endoparasitic infections such as hydatid cysts and Dicrocoelium dendriticum infection, high plasma levels of liver enzymes such as AST and ALT with low level of TP and vitamin-A were determined (25).…”
Section: Discussionsupporting
confidence: 90%
“…Thus, the graduated reduction in ALB and TP levels that are indicated in the current study seems to be associated with an increase in liver's hydatid cyst infection ratio, which may be caused by expand growing of hydatid cysts in the liver. In agreement with the current data, during endoparasitic infections such as hydatid cysts and Dicrocoelium dendriticum infection, high plasma levels of liver enzymes such as AST and ALT with low level of TP and vitamin-A were determined (25).…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the increases detected in the AST activities and total bilirubin levels of the sheep with Cystic echinococcosis (Heidarpour et al, 2012;Cinar et al, 2018), and the increase in the total protein (Ayaz et al, 2006;Sagkan-Ozturk et al, 2015) and globulin levels (Ayaz et al, 2006) are consistent with the results of the aforementioned studies. Yuksek et al (2007) report that the ALP and AST activities of sheep infected with endoparasites are higher compared to healthy animals and that the increase is caused by the necrosis or cholestasis of the hepatic cells.…”
Section: Resultssupporting
confidence: 89%
“…In a study conducted by Cinar et al (2018) indicated that there were greater AST (p<0.001), ALP (p<0.05), and total bilirubin (p<0.001) levels of sheep infected with the cyst compared to the control group. On the other hand, total protein (p<0.001) and Mg (p<0.05) levels were found to be lower.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Vitamin C may protect host cells and also reduce the rate of infection during infection diseases such as echinococcosis. However, Cinar et al in a study in 2018 reported that vitamin C plasma level in sheep naturally infected with hydatid cysts was not affected by infection (Cinar et al 2018). However, further studies are needed to determine the exact effect of ascorbic acid on E.granulosus larval stages.…”
Section: Discussionmentioning
confidence: 99%